FAKTOR – FAKTOR GEOGRAFI YANG MENDUKUNG KEGIATAN PARIWISATA PANTAI PUTERI SERAYI DI DESA JAWAI LAUT - Nurmirawati Nurmirawati; Nuraini Asriati; Diah Trismi Harjanti (Universitas Tanjungpura, 2021)
AbstractThis research was to investigate the value of tourism potential and geographical factors that support tourism activities on Puteri Serayi beach. This research provides information used as a guideline for policy formulation and management of the Puteri Serayi beach tourism destinations. The design was descriptive research with quantitative methods which was conducted in Bukit Raya, Jawai Laut. research data were derived from observations, interviews, and documentation. Techniques for data analysis used were scoring and descriptive analysis. The tourism potential values were classified into three categories : high, moderate, and low. For the potential value of natural tourism objects, the value classification is appropriate, conditionally appropriate, and inappropriate. The finding showed that the potential value of natural tourism objects score 96% (appropriate), artificial tourist attractions, accessibility, amenities respectively moderate 120, 175, and 430. The scoring indicates that the influence of geographical factors in tourism activities, specifically natural and human factors, is unbalanced, with human aspect still having shortcomings. This is emphasized by the development and management of attractions, accessibility, and amenities in RT 01 and 02, which is insufficient to support the development of the Puteri Serayi beach tourism destination.Keywords: Tourist Attraction, Accessibility, Amenity, Geographical Factor